2023
DOI: 10.3390/polym15020255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Infill Parameters on the Compressive Strength of 3D-Printed Nylon-Based Material

Abstract: 3D printing is the most suitable method to manufacture the frame parts of powered ankle-foot prostheses but the compressive strength of the 3D-printed part needs to be ensured. According to the compression test standard ASTM D695, the effect of infill pattern and density, which is transferred to the mass of the standard specimen, on the compressive strength is investigated with a carbon fiber-reinforced nylon material. With the same infill pattern, specimens with more mass have a higher compressive strength. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Hernandez et al confirmed these findings [6]. Liu et al [7] study the compressive strength of a carbon fiber-reinforced nylon material by varying the infill parameters. The conclusion is that parts with triangle infill have the highest compressive strength.…”
Section: Introductionmentioning
confidence: 81%
“…Hernandez et al confirmed these findings [6]. Liu et al [7] study the compressive strength of a carbon fiber-reinforced nylon material by varying the infill parameters. The conclusion is that parts with triangle infill have the highest compressive strength.…”
Section: Introductionmentioning
confidence: 81%
“…One of the most used fibre-reinforced composite filaments in functional 3D printing is the chopped glass or carbon fibre-reinforced nylon filaments due to their mechanical, chemical, and thermal properties [ 14 ]. Research on the effect of the infill of such materials can already be found [ 15 , 16 , 17 , 18 ], mainly due to the fact that the orientation of fibres inside the nylon should contribute to its mechanical properties significantly, and the most investigated mechanical properties are the tensile and compressive strengths of the samples, which is quite strange considering the fact that fibre reinforcement is commonly used to enhance materials’ flexural strength. However, these studies are quite limited in their scope and do not investigate other important parameters, and the choice of other parameters is hardly stated, and often when they are stated, they seem to be chosen randomly or are the factory presets, which should be modified based on a number of factors.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study performed by Ramesh and Panneerselvam, 14 the fill parameters such as fill pattern and infill density were introduced as the main effective factors in improving the ultimate tensile strength. However, Liu et al 15 showed that the triangle fill pattern with high infill density provides a better performance from a compressive strength point of view. Hsueh et al 16 reported that the mechanical performance especially the tension, bending, and compression properties of the FDM products increased as the printing temperature increased.…”
Section: Introductionmentioning
confidence: 99%